BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Plant Pathogens-The Viruses. Author, R. S. Singh, Published by Sarita Prakashan,Â Meerut and New Delhi, 176 pp. Price Rs. 50.00. Basic Research for Crop Disease Management. Editor, P. Vidhyasekaran, DayaÂ Publishing House, Delhi-1l0 006, 1990, 410 pp. Price Rs. 450.00. Â